2013
DOI: 10.1186/1744-8603-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unequal HIV care access among people living with HIV in Peru

Abstract: BackgroundEquity in access to health care among people living with HIV (PLHA) has not been extensively studied in Peru despite the fact there is significant social diversity within this group. We aimed to assess the extent to which health care provision to PLHA, including ARVT, was equitable and, if appropriate, identify factors associated with lower access.MethodsWe conducted a survey among adult PLHA in four cities in Peru, recruited through respondent-driven sampling (RDS), to collect information on socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…TW who are unaware of their HIV status may have lower access to HIV testing due to inadequate access to the formal health care system. TW in Peru have described denial of health care on the basis of their gender identity as well as stigma and discrimination when accessing HIV testing services [16, 37]. US studies have found a higher burden of stigma among TW who do not “pass,” or are not perceived by others as female without suspicion or judgment, and a better quality of life among transgender individuals who do pass [19, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…TW who are unaware of their HIV status may have lower access to HIV testing due to inadequate access to the formal health care system. TW in Peru have described denial of health care on the basis of their gender identity as well as stigma and discrimination when accessing HIV testing services [16, 37]. US studies have found a higher burden of stigma among TW who do not “pass,” or are not perceived by others as female without suspicion or judgment, and a better quality of life among transgender individuals who do pass [19, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…HIV prevalence has been reported to be as high as 12.4% (Ministerio de Salud, 2012) and 22% (Beyrer et al, 2013; Sanchez et al, 2007) in the capital city of Lima, compared to 0.2% in the general population (Garcia et al, 2012). TGW are markedly vulnerable to HIV/AIDS (Silva-Santisteban et al, 2012) and among PLH, age <35 years and being a TGW are associated with reduced healthcare access (Silva-Santisteban et al, 2013). HIV transmission among MSM/TGW in Peru is driven by unknown HIV status (Goodreau et al, 2012; Vagenas et al, 2014) and sexual risk behavior (Goodreau, Goicochea, & Sanchez, 2005), which is also correlated with AUDs and drug use (Ludford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MacCarthy et al, 2017y Socías et al, 2014 encontraron que a nivel mundial la presencia de ITS y VIH es mayor en las trans femeninas que en el resto de la población y los HSH. La creciente evidencia mundial indica que las poblaciones transgénero sufren por el VIH y otras infecciones de transmisión sexual (ITS); en particular, las mujeres transgénero que tienen Sexo con hombres y trabajadoras sexuales transgénero (Silva-Santisteban et al 2013).…”
Section: Introductionunclassified
“…La información sobre la coinfección por VIH e ITS a nivel mundial y en la región centroamericana es limitada, sin embargo, determinar la coinfección entre las trans femeninas es clave para reducir la posibilidad que éstas tienen de morir por la asociación de estas patologías (Socías et al, 2014) y (Silva-Santisteban et al 2013). Nicaragua actualmente no cuenta con registros oficiales que permitan establecer la coinfección por ITS y VIH en trans femeninas VIH positivo únicamente (Morales-Miranda et al 2014, & Sánchez, Ibarra , Tallada , Saleh-Ramírez 2013 , además éste grupo dentro de la diversidad sexual está ubicado dentro de la población de HSH, es muy disperso, no organizado lo que representa una importante limitación para la toma de decisiones en la planificación de una respuesta nacional para enfrentar el avance de la epidemia del sida a partir de las infecciones por ITS y VIH.…”
Section: Introductionunclassified